Hydrothermal surface-wave instability and the Kuramoto-Sivashinsky equation - Kraenkel, Roberto André [UNESP]; Pereira, J. G. [UNESP]; Manna, M. A. (Elsevier, 1994)
We consider a system formed by an infinite viscous liquid layer with a constant horizontal temperature gradient and a basic nonlinear bulk velocity profile. In the limit of long wavelength and large nondimensional surface tension we show that hydrothermal surface-wave instabilities may give rise to disturbances governed by the Kuramoto-Sivashinsky equation. A possible connection to hot-wire experiments is also discussed. © 1994.